Konsep Keadilan Voting dalam Rapat Penundaan Kewajiban Pembayaran Utang - yalid yalid; Irawan Harahap; Riantika Pratiwi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: To explain the contradictions of the reconciliation arrangement in the meeting voting on the Debt Payment Obligation Deferral and to formulate the concept of ideal justice voting in the Debt Payment Obligation Deferral meeting. Research methodology: This type of research is normative legal research. Results: The principle of justice in the Bankruptcy and PKPU Laws contains that provisions regarding bankruptcy can fulfill a sense of justice for interested parties. The entire analysis of the concept of justice is related to legal facts in the Bankruptcy Law and PKPU which adopt the principle of balance by stating that the principle of "fairness" is not ideal. Therefore, it is necessary to reform the principles of justice in bankruptcy law and PKPU in order to fulfill the legal ideals of bankruptcy law. The legal ideals that have been fulfilled are elements of commutative justice, but considering the differences in the criteria or portions of each, according to the author, it is necessary to renew these legal principles based on the concept of distributive justice. Then ideally the voting results should ideally be binding on all parties. Limitations: This study is only related to voting norms in the bankruptcy law and PKPU. Contribution: This research is expected to be a reference and contribution to the Government in reforming bankruptcy law and PKPU.